The development of administrative and legal science under martial law: an assessment of it's prospective direction in Ukraine - Komziuk, A. T.; Комзюк, А. Т.; Muzychuk, O. M.; Музичук, О. М.; Kobzieva, Т. A.; Кобзєва, Т. А.; Kovalov, I. M.; Ковальов, І. М.; Anatolii Komziuk (Remittances Review. – 2022. – Vol. 8, № 1. – P. 146-156, 2022)
Розвиток перспективних напрямів адміністративно-правової науки в умовах воєнного стану є елементом, який викликає бурхливі оплески, хоча й розглядає виклики та труднощі розвитку адміністративно-правової сфери в умовах кризової ситуації воєнного стану, коли традиційні правові рамки можуть не бути достатнім. Враховуючи надзвичайні заходи, вжиті під час воєнного стану, важливо вивчити правову базу, яка регулює такі ситуації, і дослідити роль адміністративного права в забезпеченні підзвітності, прозорості та захисту основних прав. Ця стаття присвячена тому, як правова система може адаптуватися до сучасних викликів воєнного стану. Розглядаються перспективні напрями розвитку адміністративно-правової науки в умовах воєнного стану, наприклад, забезпечення відповідності правової системи потребам суспільства.

Developing a promising directions of administrative and legal science under martial law is element that attracts huge applause even though it considers the challenges and difficulties of the development of the administrative and legal sphere in the conditions of a crisis situation martial law, when traditional legal frameworks may not be sufficient. Given the emergency measures taken during martial law, it is important to examine the legal framework governing such situations and explore the role of administrative law in ensuring accountability, transparency and the protection of fundamental rights. This article focuses on how the legal system can adapt to the modern challenges of martial law. Promising directions for the development of administrative and legal science under martial law are considered, for example, ensuring the compliance of the legal system with the needs of society.

В данной статье основное внимание уделяется тому, как правовая система может адаптироваться к современным вызовам военного положения. Рассмотрены перспективные направления развития административно-правовой науки в условиях военного положения, например, обеспечение соответствия правовой системы потребностям общества.
Keywords: Україна; publikatsii u WoS; martial law regime; administrative law; state administration; legal systems; political regime; administrative legislation; Ukraine; режим воєнного стану; адміністративне право; державне управління; правова система; політичний режим; адміністративне законодавство; Украина; режим военного положения; административное право; государственное управление; правовая система; политический режим; административное законодательство